(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mirzazadeh A, Pourbabaei H, Daryaei MG, Bonyad A. 2022. Effects of plot size on assessment of tree species diversity in Caspian forests of Iran. Biodiversitas 23: 4879-4886. Tree species diversity is important to forest managers because any management that reduces tree species diversity may greatly reduce commercial benefits. Therefore, control over tree species diversity is an important aspect of hardwood forest management. An efficient and quick survey method is needed to facilitate the assessment of tree species diversity in forest stands. In this study, the effects of plot size on the assessment of tree species diversity were compared in the uneven-aged hardwood stands in the Hyrcanian forests of Iran. There were selected 50 hectares of these forests representing the regional forests. Sampling procedures were carried out on concentric lozenge plots with different sizes, including 400, 800, 1000, 1200, 1600, 2000, 2500, and 5000 m2 in the dimensions of 150×150m. For each plot, the type of the species and the number of trees were recorded. Shannon-Wiener (H’), Simpson (1-D), Mc-Arthur (N1), Hill (N2), Camargo (E’), Simpson (E1/D), Nee (EQ), Smith-Wilson (Evar), Menhinick (R2), Margalef (R1) indices were used to estimate of tree species biodiversity. The precision and cost criteria (E%2× T) were applied for a better evaluation of different plot sizes. The obtained inventory error values showed that Hill (diversity), Camargo (evenness) and Menhinick (richness) indices had the lowest inventory error in the different plot sizes. Also, the lowest value of inventory error in diversity, evenness and richness indices were related to plot sizes of 2500, 5000, and 5000 m2, respectively. Based on the obtained results of diversity and evenness indices, there was a significant difference between the different plot sizes and different indices. The results showed that the lowest value of E%2×T for diversity, evenness and richness was related to Hill (800 m2), Camargo (1000 m2), and Menhinick (400 m2). The finding results revealed that plot size had a significant effect on tree species’ evenness.